STUDY ON THE CONSERVATION OF BIODIVERSITIES & GENETIC EVOLUTION OF TASAR SILK WORM ANTHERAEA MYLITTA D. (SATURNIIDAE: LEPIDOPTERA) (International Journal of Food and Nutritional Sciences, 2023)
Tassar Silk, often referred to as wild silk, comes from the Antheraea moths. It is of two types:Tropical and Temperate.China is the largest producer of Tassar silk in the world followed by India.China produces only Temperate Tassar silk while India has got distinction in producing bothtropical and temperate varieties